(untitled) (Linguostylistic Studies, 2021)
The article elucidates the time-space markers in the story Sanatorium under the Hourglass by Bruno Schulz in its translation into Ukrainian by Yurii Andrukhovych. The value of other translations of the work into Ukrainian is analyzed at the level of their image-creation system. The main time-space markers of the writer’s artistic thinking and their translation interpretations are determined. The author identifies the parallels between the author’s imaginative world and the real events from his life. Special attention is paid to the markers of a city, a sanatorium, a train, and an hourglass. The writer’s world in the biographical dimension is centered round the Galician city of Drohobych. The childhood and youth associated with Galicia are present in every Schulz’s work. This is especially noticeable in the images of father, mother, his maid who have distinct biographical features in all the stories of the collection “Sanatorium under the Hourglass”. The story deals with the biography and real-time which the writer seeks to convey to his characters. At the same time, Schulz’s work, both in the original and in the translated Ukrainian version, reproduces the past which, as the author notes himself, cannot be returned unless we recreate it in memories. The dream marker brings the reader to the labyrinths of memory, leads them as if through the streets of the city. Lyrical hero Józef, with whom the writer constantly associates himself, brings him back to his childhood and youth, trying to recreate the past worldview and the already lost world. Feelings of sadness and separation are read in each fragment of the story. Thus, we can confirm that the translator Yurii Andrukhovych skillfully conveys the emotions and feelings created by the author in the original. The hourglass is a symbol of the reverse time which makes the main hero of the work look like a demiurge and the markers of it are a mythical city from the past and a mythical hospital – a sanatorium where some fantastic events take place. There, the dead stay alive as long as a memory about them exists. They re-live the events of their life – work, rest, war, and so on. This is a vicious circle they cannot run away from, the only exception is the protagonist. It is noteworthy that the image of the hourglass is missing in the work, and it appears only in the title of the story. Such manipulation with images is characteristic of Schulz and Kafka, but the difference between these writers is significant. In contrast to Kafka’s pessimism, we trace Schulz’s invincible positivism which travels by the train of time at breakneck speed and fights for life with all its might. This option is confirmed by the motive of wandering around the city and trying to escape from the dog-man that at any moment can cause the destruction and catastrophe to the world established in sanatorium. The image of the sanatorium is airtight. It is complemented by the image of a Doctor who influences the establishment of the return time. The author shares the opinion of the Polish literary critics and researchers of Schulz’s work who argue that the main character of the story “Sanatorium under the Hourglass” is time itself in all its mythical and real dimensions.